PENGARUH PENGGUNAAN MEDIA INTERAKTIF BERBASIS WEBSITE EDUCAPLAY TERHADAP HASIL BELAJAR MATEMATIKA PADA NILAI TEMPAT BILANGAN SISWA KELAS III SDN WALURAN - Yuni; Hilman Hilmawan; Ajeng Lestari; Yuliyanti; Gina Farida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low mathematics learning outcomes of students on place value material indicate that their conceptual understanding has not been optimal. One factor contributing to this condition is the use of less interactive learning media, which results in students being less actively involved in the learning process. Therefore, learning media that can increase student engagement are needed, one of which is the educaplay website, which provides various interactive learning activities. This study aimed to determine the effect of interactive learning media based on the educaplay website on the mathematics learning outcomes of third-grade students at SDN Waluran in place value material. This study employed a quantitative approach using a pre-experimental method with a One Group Pretest-Posttest Design. The sample consisted of 30 third-grade students selected through saturated sampling. Data were collected through learning achievement tests and analyzed using the normality test, Paired sample t-test, and N-Gain test. The results showed that the mean pretest score of the students was 52.83, which increased to 79.50 in the posttest. The Paired sample t-test yielded a significance value of 0.001 < 0.05, indicating that H₀ was rejected and Hₐ was accepted. In addition, the N-Gain test results indicated an improvement in learning outcomes in the moderate category. Therefore, it can be concluded that the use of interactive learning media based on the educaplay website has a positive and significant effect on mathematics learning outcomes in place value material among third-grade students at SDN Waluran.